Living permanent liminality: the recent transition experience in Ireland - Szakolczai, Arpad (Irish Journal of Sociology, 2014)
Modernity, or the combination of market economy, liberal democratic polity and a society driven by technological progress, we are led to believe, is the end-state of history; the glorious condition of a fully enlightened society of free citizens equipped with equal rights at which all traditional societies are bound to arrive, after a period of transition which might involve some temporary difficulties or 'sacrifices'. However, and in contrast to this, modernity rather involves an infinite period of transition, in which the stable elements of social life, representing not just rigid external constraints on individual freedom, but also the condition of possibility of meaningful life, are one by one liquidated. This article argues that the anthropological concept 'liminality' is particularly helpful in understanding the formative aspects of transition experiences, like the Celtic Tiger phenomenon in Ireland. It also helps to move beyond the conventional 'transition to modernity' framework by pointing out that advanced modernity is identical to a permanent state of transitionality.
Sociology
Keywords: FOUCAULT; Michel; 1926-1984; Ireland; POLANYI; Karl; 1886-1964; capitalism; genealogy; liminality; manners & customs; modern society; modernity; technological innovations & economics; tradition; trickster